(3aJM GdYbjOI aj TQM GdbUjOIs - (3YHO Gddg Hf Ydj Hf eMeO Hf CHi GdbGSe Hf eMeO Hf LYaQ Hf eMeO Hf GdMSjfs; (3MeRI Hf CHj GdbGSe Hf eMeO Hf LYaQ Hf GdgGOj Gdj GdMbs
(3ChdgG (B:s
(3CeG HYO , adeG cGfJ gPg GdbUjOI EfTGA ehdGfG MeRRg Hf CHj GdbGSe eJVefI YbjOI BjGJg aQCjJ QYGjI aVdI HcTa eYGfjgG s
(3BNQgG (B:s
(3Ke bGd EfeG jQjO Gddg djPgH Yfce GdQLS Cgd GdHjJ , aOd gPG Ydi Cf Cgd GdHjJ Ydjge GdSdGe ge Ydi haGWeg hGdMSf hGdMSjf hCHfGDge s
(3efXheIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds